Editorial: Special Issue contributed by the 10th International Chemical and Biological Engineering Conference - CHEMPOR 2008 - Ferreira, Eugénio C. (2009)
The 10th International Chemical and Biological Engineering Conference - CHEMPOR 2008, was held in Braga, Portugal, from the 4th to the 6th of September, 2008. The conference was jointly organized by the University of Minho, the “Ordem dos Engenheiros,” and the Institute for Biotechnology and Bioengineeing, with the support of “Sociedade Portuguesa de Qu´ımica” and “Sociedade Portuguesa de Biotecnologia”. The CHEMPOR series traditionally brings together both young and established researchers and end users to discuss recent developments in different areas of Chemical Engineering. The scope of this edition was extended to Biological Engineering research. One of the major core areas of the conference program was life quality, due to the importance that Chemical and Biological Engineering plays in this area. “Integration of Life Sciences & Engineering” and “Sustainable Process-Product Development through Green Chemistry” were two of the leading themes with papers addressing such important issues. This was complemented with additional leading themes including “Advancing the Chemical and Biological Engineering Fundamentals,” “Multi-Scale and/or Multi-Disciplinary Approach to Process-Product Innovation”, “Systematic Methods and Tools for Managing the Complexity”, and “Educating Chemical and Biological Engineers for Coming Challenges.” Papers contributed for this special issue represent a good sample of the important themes that were addressed. This special issue presents a set of fifteen selected research papers, which have undergone the peer-review process of Chemical Product and Process Modeling journal. We wish to thank the authors who have contributed to yield a high scientific standard to this special issue. We also extend our gratefulness to all reviewers, through their dedicated efforts, having assisted us in this task.